Neurodiversity in entrepreneurship - Marino, Louis D.; Corbett, Andrew C.; Lerner, Daniel A. (Advances in entrepreneurship, firm emergence and growth, 2025)
Anecdotal evidence suggests that entrepreneurship is a context in which individuals who see and/or experience the world differently can drive innovation and invention in ways that create wealth and enhance the public good. The chapters in this volume leverage comprehensive theoretical frameworks, empirical evidence, and interdisciplinary methodologies to advance our understanding of neurodiversity in entrepreneurship. The chapters employ diverse approaches and collectively establish how neurodivergent individuals create value within entrepreneurial contexts, moving beyond deficit-based conceptualizations and demonstrating how to harness cognitive differences as entrepreneurial strengths, while thoughtfully addressing associated challenges. The collection of prominent researchers in this volume focuses on diverse topics at the intersection of neurodiversity and entrepreneurship, but three primary theses emerge from their collected works. First, neurodivergent traits can enhance performance in the entrepreneurial context despite the unique challenges presented by various types of neurodiversity. Second, the neurodiversity of individual team members can improve collective performance beyond that of neurotypical teams through intentional team design and appropriate support structures. Finally, the integration of interdisciplinary methodologies, such as neuroscience, social identity theory, and entrepreneurship research, can enable us to examine unexplored intersections and better understand the implications of the neurobiological underpinnings of entrepreneurs' cognitions, as well as the intersection of topics like gender and neurodiversity in the entrepreneurial context. Taken together, these theses argue for positioning neurodiversity as not a side issue, but as one that is central to understanding modern entrepreneurship. Advances in Entrepreneurship, Firm Emergence and Growth (AEFEG) provides an annual examination of the major current research theoretical and methodological efforts in the field of entrepreneurship and its related disciplines of small business family business and population ecology as well as firm growth and emergence research.